CRANIOPHARYNGIOMA: A CASE WITH DELAYED PUBERTY - Ali, Syed Khawar; Hashim, Rizwan; Khan, Farooq Ahmad (Pakistan Armed Forces Medical Journal, 2011)
Craniopharyngiomas are benign and aggressive epithelial neoplasms, comprising approximately 3% of all intracranial tumors1. These are the most common childhood tumor involving the hypothalamus and pituitary2. Endocrine disturbances may present in 80-90% of patients. Hormonal studies show growth hormone (GH) deficiency in 75% of children, deficiencies of LH/FSH in 40%, ACTH in 25% and TSH in 25% of cases2.Resonance Imaging) that showed its location in Sellar and supra sellar regions with rim enhancement causing obstruction and dilatation of right lateral ventricle. Relevant laboratory investigation results are given in the table.